Hygiene in Primary Schools: Perspectives on The Writings of Antonio Ferreira de Almeida Júnior (1922-1939) - Pall Oriani, Angélica (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
The purpose of this paper is to analyze how hygiene and education were drawn together in bibliographical production and in the professional work of Antonio Ferreira de Almeida Júnior (1892-1971), a teacher, physician, and education manager who wrote teaching manuals oriented towards hygiene, childcare, and educational biology. In them, Almeida Júnior nuanced representations about the nature of the child in relation to the primary school’s role in improving society’s health, and assigns key importance to teachers, who were taught medical practices and instructed to measure children’s height and weight, and to check teething, hair, vision, and hearing. Healthy habits were verified in order to consolidate them among children, identifying them as either healthy or ill and classifying children as "normal" and "abnormal."